TSLP is differentially regulated by vitamin D3 and cytokines in human skin. Issue 1 (16th February 2015) - Landheer, Janneke; Giovannone, Barbara; Sadekova, Svetlana; Tjabringa, Sandra; Hofstra, Claudia; Dechering, Koen; Bruijnzeel‐Koomen, Carla; Chang, Charlie; Ying, Yu; de Waal Malefyt, Rene; Hijnen, DirkJan; Knol, Edward
Abstract: Thymic stromal lymphopoietin (TSLP) plays an important role in allergic diseases and is highly expressed in keratinocytes in human lesional atopic dermatitis (AD) skin. In nonlesional AD skin TSLP expression can be induced by applying house dust mite allergen onto the skin in the atopy patch test. Several studies have demonstrated that the induction of TSLP expression in mouse skin does not only lead to AD‐like inflammation of the skin, but also predisposes to severe inflammation of the airways. In mice, TSLP expression can be induced by application of the 1, 25‐dihydroxyvitamin D3 (VD3) analogue calcipotriol and results in the development of eczema‐like lesions. The objective is to investigate the effect of VD3 (calcitriol) or calcipotriol on TSLP expression in normal human skin and skin from AD patients. Using multiple ex vivo experimental setups, the effects of calci(po)triol on TSLP expression by normal human skin, and skin from AD patients were investigated and compared to effects of calcipotriol on mouse and non‐human primates (NHP) skin. No induction of TSLP expression (mRNA or protein) was observed in human keratinocytes, normal human skin, nonlesional AD skin, or NHP skin samples after stimulation with calcipotriol or topical application of calcitriol. The biological activity of calci(po)triol in human skin samples was demonstrated by the increased expression of the VD3‐responsive Cyp24a1 gene. TSLP expression was induced by cytokines (IL‐4, IL‐13, and TNF‐α) in skin samples from all three species. In contrast to the findings in human and NHP, a consistent increase in TSLP expression was confirmed in mouse skin biopsies after stimulation with calcipotriol. VD3 failed to induce expression of TSLP in human or monkey skin in contrast to mouse, implicating careful extrapolation of this often‐used mouse model to AD patients. Abstract : Vitamin D3 has been shown to induce eczema‐like inflammation and TSLP expression in mouse skin. However, we show that using multiple experimental setups, vitamin D3 does not induce TSLP expression in normal human skin and skin from atopic dermatitis (AD) patients.